XXI Secolo : Arte e Architettura. - Hoet, Jan; Pieroni, Mario; Di Pietrantonio, Giacinto; Sartorelli, Avv. Carlo (Roma : Zerynthia - Associazione per l'arte Contemporanea Roma, 1995)
Accardi, Carla ; Airo, Mario ; Battista, Nicola Di ; Beecroft, Vanessa ; Berti, Remo ; Botta, Mario ; Bourriaud, Nicholas ; Capanna, Ilvi ; Cascella, Anna ; Cucchi, Enzo ; Dardano, Giò ; Delvoye, Wim ; Ferraris, Giorgio ; Garutti, Alberto ; Gillick, Liam ; IRWIN ; Kopystianskaya, Svetlana ; Kozaris, Dimitris ; Leggeri, Tullio ; van der Linden, Barbara ; Mils, Patrick ; Pichler, Mariano ; Pieroni, Mario ; Pirri, Alfredo ; Pisani, Vettor ; Pistoletto, Michelangelo ; Purini, Franco ; Quartana, Luca ; Robbrecht, Paul ; Rota, Italo ; Scaglione, Pino ; Scuderi, Massimiliano ; Serino, Roberto ; Spalletti, Ettore ; Taglietti, Stefano ; Vaerini, Bruno ; West, Franz ; Zanmatti, Alberto ; Zevi, Luca
The international convention "21st Century" which took place September '94 in Silvi Marina, on the Abruzzo coast, brought together artists and architects as well as academics of various disciplines, to debate the actual relationship between art and architecture and whether it would be possible to rejuremate a cohesion between them, something that already existed at the time of the Renaissance but was later lost.
Italiaans & Engels
boek